Plasma membrane recovery kinetics of a microfluidic intracellular delivery platform - Sharei, Armon (2014)
Intracellular delivery of materials is a challenge in research and therapeutic applications. Physical methods of plasma membrane disruption have recently emerged as an approach to facilitate the delivery of a variety of macromolecules to a range of cell types. We use the microfluidic CellSqueeze delivery platform to examine the kinetics of plasma membrane recovery after disruption and its dependence on the calcium content of the surrounding buffer (~5min without calcium vs. ~30s with calcium). Moreover, we illustrate that manipulation of the membrane repair kinetics can yield up to 5x improvement in delivery efficiency without significantly impacting cell viability. Membrane repair characteristics initially observed in HeLa cells are shown to translate to primary naïve murine T cells. Subsequent manipulation of membrane repair kinetics also enables the delivery of larger materials, such as antibodies, to these difficult to manipulate cells. This work provides insight into the membrane repair process in response to mechanical delivery and could potentially enable the development of improved delivery methods.